Fasudil, a Rho-Kinase Inhibitor, Exerts Cardioprotective Function in Animal Models of Myocardial Ischemia/Reperfusion Injury: A Meta-Analysis and Review of Preclinical Evidence and Possible Mechanisms - Huang, Yue-yue; Wu, Jian-ming; Su, Tong; Zhang, Song-yue; Lin, Xiao-ji (Frontiers in Pharmacology, 2018)
Fasudil, a Rho-kinase inhibitor, has shown outstanding therapeutic effects against cerebral vasospasm after subarachnoid hemorrhage (SAH) in humans. Studies show various biological effects of fasudil in the cardiovascular system. We conducted a preclinical systematic review to determine the efficacy and possible mechanisms of fasudil on animal models of myocardial ischemia/reperfusion (I/R) injury. Nineteen studies involving 400 animals were identified after searching 8 databases for articles published till June 2018. The methodological quality was assessed by the Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies (CAMARADES) 10-item checklist. The data were analyzed using Rev-Man 5.3 software, and the score of study quality ranged from 3 to 6 points. Compared to the control group, fasudil treated animals showed reduced myocardial infarct size (P< 0.05), lower levels of cardiac enzymes (P< 0.05) and cardiac troponin T (P< 0.05), improved systolic and diastolic functions (P< 0.05), and increased degree of decline in the ST-segment (P< 0.05). The possible mechanisms of fasudil action against myocardial I/R injury are improvement in coronary vasodilation, inhibition of apoptosis and oxidative stress, relieving inflammation, and reduction in endoplasmic reticulum stress and metabolism. In conclusion, fasudil exerts a cardio-protective function through multiple signaling pathways in animal models of myocardial I/R injury.